2020
DOI: 10.1111/pan.13879
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative apnea in infants with hypertrophic pyloric stenosis: A systematic review

Abstract: Background Infantile hypertrophic pyloric stenosis (IHPS) leads to excessive vomiting and metabolic alkalosis, which may subsequently cause apnea. Although it is generally assumed that metabolic derangements should be corrected prior to surgery to prevent apnea, the exact incidence of perioperative apneas in infants with IHPS and the association with metabolic alkalosis are unknown. We performed this systematic review to assess the incidence of apnea in infants with IHPS and to verify the possible association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In this study, we found an incidence of postoperative apnea of 3.0%, which is in line with the results of 0.2 to 16% in a recent systematic review. 7 The total incidence of postoperative respiratory events, consisting of desaturation, stridor, hypopnea, and apnea was 21.2%. We found that infants who underwent open pyloromyotomy had more often a period of perioperative hypoxemia and less often postoperative respiratory events compared to infants who underwent a laparoscopic procedure.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this study, we found an incidence of postoperative apnea of 3.0%, which is in line with the results of 0.2 to 16% in a recent systematic review. 7 The total incidence of postoperative respiratory events, consisting of desaturation, stridor, hypopnea, and apnea was 21.2%. We found that infants who underwent open pyloromyotomy had more often a period of perioperative hypoxemia and less often postoperative respiratory events compared to infants who underwent a laparoscopic procedure.…”
Section: Discussionmentioning
confidence: 94%
“…6 In a recent literature review, we showed an incidence of postoperative respiratory events in infants with IHPS of 0.2 to 16%. 7 However, this review was hampered by a small number of included patients and the lack of studies that primarily investigated the occurrence of apnea in infants with IHPS. In addition, the included studies used different definitions of apnea that led to heterogeneous results regarding the occurrence of postoperative respiratory events.…”
Section: Introductionmentioning
confidence: 99%
“…There are at least two case reports regarding preoperatively apneic infants with pyloric stenosis [4] [12]. However, the detailed trigger and incidence of pre-or postoperative apnea in pyloric stenosis are not well known [13].…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous fluid therapy in pyloric stenosis must correct metabolic alkalosis, which increases the risk of apneas in the postoperative period. 3,[7][8][9] It should provide the right amount of sodium so as not to lead to postoperative hyponatremia with all its consequences (including vomiting). Because of the high risk of hypoglycemia in infants, it should also provide enough glucose.…”
Section: Discussionmentioning
confidence: 99%